Behavior of rr soybeans subjected to different formulations and rates of glyphosate in the reproductive period - Albrecht, A. J. P.; Albrecht, L. P.; Krenchinski, F. H.; Placido, H. F.; Lorenzetti, J. B.; Victoria Filho, R.; Barroso, A. A. M. [UNESP] (Univ Federal Vicosa, 2014)
Recent studies indicate that glyphosate applied in post-emergence in RR soybean can eventually cause phytotoxic effects. However, there are many questions that need to be clarified in the scientific and technical contexts, involving the issue of RR soybeans regarding the use of glyphosate. This study has assessed the impact of the application of different doses and formulations of glyphosate in the reproductive period of RR soybean (R1 stage). For that purpose, an experiment in the field was conducted in two harvests (2011/12 and 2012/13), in which a 2 x 5 factorial design was used (formulations versus doses) totaling 10 treatments. In these two experiments the variables related to agronomic performance were: phytotoxicity (7, 14, 21 and 28 days after application), plant height, number of pods per plant, yield and weight of 100 grains (end of soy cycle). The results obtained allowed characterizing phytotoxicity and damages to the height and yield in RR soybean, with increasing rates of glyphosate applied in the reproductive period.

Resultados de pesquisas recentes indicam que o glyphosate aplicado em pós-emergência na soja RR pode, em algumas situações, gerar efeitos fitotóxicos. Entretanto, persistem muitas dúvidas que precisam ser melhor elucidadas no âmbito científico e técnico, envolvendo a questão da soja transgênica (RR), sobre aplicação de glyphosate. Desse modo, o presente trabalho teve por objetivo avaliar o impacto da aplicação de diferentes doses e formulações de glyphosate, no período reprodutivo da soja RR (estádio R1). Para isso, foi conduzido um experimento no campo, por duas safras (2011/12 e 2012/13), em que foi utilizado arranjo fatorial 2 x 5 (formulações x doses), totalizando 10 tratamentos. Nesses dois experimentos, as variáveis relacionadas ao desempenho agronômico foram: fitointoxicação (7, 14, 21 e 28 dias após a aplicação), altura de plantas, número de vagens por planta, produtividade e massa de 100 grãos (final do ciclo da cultura). Os resultados alcançados caracterizaram progressiva fitointoxicação e danos à altura e produtividade da soja RR, com o incremento das doses de glyphosate aplicadas no período reprodutivo.
Comportamento da soja RR submetida à aplicação de diferentes formulações e doses de glyphosate no período reprodutivo
Keywords: Glycine max; Herbicide; Transgenic crops; Phytotoxicity; Glycine max; herbicida; culturas transgênicas; fitotoxicidade